Numerical Investigation of Heat Transfer on Geometry Parameters in Swirl Flow Jet Impingement - Wai O.J.; Gunnasegaran P.; Hasini H. (American Institute of Physics Inc., 2024)
Heat transfer enhancement is vital in the technological dependence era in every aspect of life, particularly in engineering applications and industry. In this paper, numerical investigation is conducted on the geometrical parameters of jet impinging system with twisted tape as swirl generator. The focus of this research is the average Nusselt number on the heated plate, effect of different value of Reynolds number, jet-to-plate distance (L/D) and twisted tape ratio (y/w) which are inserted in the jet nozzle. The numerical simulations are performed at four different Reynolds number of 4000, 8000, 12000 and 16000, four (L/D) which is 2, 4, 6 and 8, and also four different (y/w). The grid independent test is conducted based on the average plate temperature to obtain optimal grid number without affecting the numerical results. The outcomes of this research are in line with the previous reported journals of similar scope of study. It is observed that, under similar operating conditions, swirling impinging jet (SIJ) offer better heat transfer rate with higher Nusselt number which performed 18.98% better than conventional impinging jets (CIJ). Finally, the best heat transfer enhancement based on the highest average Nusselt number over the heated plate is obtained with high twist ratio at 7, high Reynold number at 16000 and also high jet-to-plate distance at 8. 2023 American Institute of Physics Inc.. All rights reserved.